2016
DOI: 10.1590/0103-6440201600678
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Blood on the Accuracy of Raypex 5 and Root ZX Electronic Foramen Locators: An In Vivo Study

Abstract: The aim of this study was to evaluate in vivo the accuracy of the Raypex 5 and Root ZX electronic foramen locators (EFLs) in the presence of blood in the root canal space. Forty single-canal teeth scheduled for extraction were selected. Access cavity was prepared and coronal enlargement was carried out. Approximately two drops of blood were collected by finger prick and injected into the root canal space. The electronic working length (EWL) of each tooth by each device was established twice before (NB group) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…Khandewal et al [14] conducted comparative evaluation of accuracy of Raypex5 and Apex NRG XFR EALs with conventional radiography in ex vivo study. They obtained the same accuracy in determining the WL for both EALs when compared with radiography Saatchi et al [52] tested Raypex 5 and Root ZX in the presence of blood and also found no significant differences. Al-Hadlaq [53] evaluated the accuracy of the Root ZX and two compact apex locators, the Root ZX mini and Mini Apex Locator, in the presence of different endodontic solutions, including 2% CHX and NaOCl at 5.25, 2.625, and 1% concentrations.…”
Section: Discussionmentioning
confidence: 92%
“…Khandewal et al [14] conducted comparative evaluation of accuracy of Raypex5 and Apex NRG XFR EALs with conventional radiography in ex vivo study. They obtained the same accuracy in determining the WL for both EALs when compared with radiography Saatchi et al [52] tested Raypex 5 and Root ZX in the presence of blood and also found no significant differences. Al-Hadlaq [53] evaluated the accuracy of the Root ZX and two compact apex locators, the Root ZX mini and Mini Apex Locator, in the presence of different endodontic solutions, including 2% CHX and NaOCl at 5.25, 2.625, and 1% concentrations.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have showed that EALs often present inaccurate results, when fluids and blood are present in the root canal, 25,26 assuming that a root canal with vital tissue may demonstrate a different impedance compared to a necrotic one. It is important to note that those studies used previous generations of EALs that had limitations on accuracy.…”
Section: Foramen Constrictionmentioning
confidence: 99%
“…Since blood is electrolyte, it may influence the accuracy of EALs. Saatchi et al 26 reported that the accuracy of Root ZX decreased slightly in the presence of blood in the root canal. In a study with 36 extracted teeth, Ebrahim et al 27 observed that in the presence of sodium hypochlorite, the apex locator Root ZX II was more accurate, than when used in a root canal filled with blood.…”
Section: Foramen Constrictionmentioning
confidence: 99%
“…Ravanshad et al (17) evaluated the accuracy of the WL with Raypex 5, being acceptable in 90% of the cases in the final obturation. In root canals with the presence of blood, Saatchi et al (24) observed the accuracy of 86.2% for Root ZX and 83.3% for Raypex 5, with a range of +0.5 mm from AF.…”
Section: Discussionmentioning
confidence: 99%